2013
DOI: 10.1371/journal.pone.0060895
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic Chaperonin CCT/TRiC and Cancer Cell Proliferation

Abstract: The molecular chaperone CCT/TRiC plays a central role in maintaining cellular proteostasis as it mediates the folding of the major cytoskeletal proteins tubulins and actins. CCT/TRiC is also involved in the oncoprotein cyclin E, the Von Hippel-Lindau tumour suppressor protein, cyclin B and p21ras folding which strongly suggests that it is involved in cell proliferation and tumor genesis. To assess the involvement of CCT/TRiC in tumor genesis, we quantified its expression levels and activity in 18 cancer, one n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 39 publications
4
54
0
Order By: Relevance
“…Its expression is regulated by the signaling downstream tot the PI3K pathway. According to recent data, the TCPA appears necessary for the in vitro and in vivo survival and growth of breast cancer cells [165,166]. An increased level of it (2.5x) was detected in the tumors.…”
Section: Tcp-1-alpha Tcpa (Tcp1)mentioning
confidence: 97%
“…Its expression is regulated by the signaling downstream tot the PI3K pathway. According to recent data, the TCPA appears necessary for the in vitro and in vivo survival and growth of breast cancer cells [165,166]. An increased level of it (2.5x) was detected in the tumors.…”
Section: Tcp-1-alpha Tcpa (Tcp1)mentioning
confidence: 97%
“…Reduction of the CCT or CCT subunit could result in growth arrest, with significant alterations in cell morphology and motility [14]. Moreover, the CCT proteins promote the development of several tumor types, including breast cancer [4], colorectal cancer [7,24,27,28], uterine sarcoma [21], lung carcinoma [8,24], ovarian cancer [22], and multitudinous tumor cells [1,25]. Recent studies have suggested that CCT8 might be upregulated in colon, breast and hepatocellular carcinoma specimens [17,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TRiC has been suggested to play a role in cancer cell development by modulating the folding and activity of client proteins involved in oncogenesis, such as the tumor suppressor proteins Von Hippel-Lindau (VHL) (20,21) and p53 (22), as well as the prooncogenic protein STAT3 (signal transducer and activator of transcription 3) (23). Of note, the expression levels of TRiC in leukemic cells are higher than in normal hematopoietic cells (24), suggesting a potential contribution of TRiC to leukemogenesis through its interactions with leukemia-causing oncoproteins.…”
mentioning
confidence: 99%